Perbedaan Hasil Belajar Matematika Siswa Berdasarkan Gaya Belajar dan Gender - Baso Intang Sappaile; Bernard; Washilah Wahdiah Ramadhani Nur (Issues in Mathematics Education (IMED), 2023)
This research aims to know the difference of students’ mathematics learning outcomes based on their learning styles and genders. This research is ex-post facto. The population is all students of grade VIII at MTsN Barru in the even semester of the 2021/2022 academic year. The sampling technique is total sampling. The instruments used in this research are mathematics learning outcomes test and learning styles questionnaire. The collected data is analyzed using descriptive and inferential statistical analysis. The results show that (1) there is a significant difference of mathematics learning outcomes between visual, auditory, and kinesthetic students, (2) the mathematics learning outcomes of female students are higher than male students but it is not significant, (3) there is no difference of mathematics learning outcomes between male and female students based on the learning styles.